(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In the modern conditions of the development of the national economy, it is of particular importance to stimulate the innovative component of entrepreneurship to increase business efficiency. Traditional ways of doing business in many countries do not fully correspond to the development trends of international business. One of the modern ways of doing business is e-commerce. E-commerce is used as a rapid means of transforming the world into an information society, expanding the concept of business from a simple transactional approach to a broader collaborative concept. The article discusses the role of e-commerce in the development of companies in the context of the digital economy.